The determinants of disagreement between the FOMC and the Fed's staff: New insights based on a counterfactual interest rate - Hamza Bennani; Tobias Kranz; Matthias Neuenkirch (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2017)
We examine the degree and sources of disagreement between the Federal Open Market Committee (FOMC) and the Federal Reserve's (Fed's) staff about the appropriate policy rate for the period 1987-2011. For that purpose, we compute a counterfactual interest rate for the Fed's staff , based on its own Greenbook forecasts and a Taylor (1993) rule, and compare it with the actual target rate. First, we find that the FOMC behaved more hawkish (dovish) during the 1990s (during the early 2000s) compared to the suggestions of the Fed's staff. Second, we reveal that a higher share of hawkish dissents, a higher share of voting women, a more experienced FOMC, and a higher share of members with a background in finance, the government, or the Bank staff are associated with relatively more hawkish monetary policy. In addition, the FOMC is found to prefer tighter monetary policy under a Democratic President, if there is a clear majority in the Congress, and during tranquil times.
Keywords: E52; E58; 330; Disagreement; Federal Open Market Committee; Federal Reserve Staff; Monetary Policy; Taylor Rule